EKSISTENSI EKSTRAKURIKULER DRUM BAND DI SEKOLAH DASAR SE-PONTIANAK TENGGARA - Nurhayaningsi Nurhayaningsi; Imam Ghozali; Nurmila Sari Djau (Universitas Tanjungpura, 2021)
AbstractThe background of the research is the researcher interest toward the existence of Drum band extracurricular at Elementary School in Southeast Pontianak which still unknown due to the unavailable data of the total unit, the condition, and other data. The purpose of this research were 1) to describe the history of drum band in Elementary School in Southeast Pontianak. 2) to describe the composition of drum band unit in Elementary School in Southeast Pontianak. 3) to describe the rehearsal activities and the achievement in Elementary School in Southeast Pontianak. The methodology of this research is descriptive research with qualitative research. The data was taken from several techniques namely observation technique, interview technique, and documentation study. The technique to validate the data was the extension of the observation and triangulation technique. The result of this research were 1) the history formed of drumband in each school had average reasons. 2) the unit composition in drumband extracurricular in each school had different of composition. 3) The achievemnts in the Drum Band in elementary schools in southeast Pontianak are different, this is influenced by several factors, namely the training system, student interest, the composition of instrument, and school activeness in participating in competition.Keywords: existence, drumband, extracurricular